Analysis of Factors Affecting Income Red Onion Farming in Woha District, Bima Regency - Ardin Irawan; M. Yasin; Muh. Hamsyuni (Doktoral Ilmu Manajemen, Universitas Pasundan, 2023)
This research aims to determine the income of red onion farming and to examine the influence of factors such as land area, capital, labor, production, and prices on red onion farming income in the Woha District, Bima Regency. The study was conducted in the Woha District, Bima Regency, from August to September 2023. The sample size of respondents in this study was 34 individuals determined through Proportional Random Sampling technique. Primary data were collected through observation, interviews, and documentation. To achieve the research objectives, multiple linear regression analysis was employed using the SPSS program. The research results indicate that the average revenue of red onion farming in the Woha District, Bima Regency, per production cycle is Rp. 70,100,735, with average expenses of Rp. 39,267,367 and average income of Rp. 30,833,368. Simultaneously, factors such as land area (X1), capital (X2), labor (X3), production (X4), and prices (X5) significantly influence the income (Y) of red onion farming in the Woha District, Bima Regency, with a coefficient of determination (R2) of 99.9%. Partially, factors such as land area (X1), capital (X2), production (X4), and prices (X5) significantly affect the income (Y) of red onion farming in the Woha District, Bima Regency, while labor (X3) does not have a significant impact.